399 Advanced Practice Provider Perspectives on Advanced Care Planning. (April 2022) - Johnson, Christopher; Colley, Alexis; Broering, Jeanette; Bongiovanni, Tasce; Roman, Sanziana; Wick, Elizabeth
Abstract : OBJECTIVES/GOALS: Perioperative surgical care is team-based with close partnership between surgeons, residents, advanced practice professionals (APPs), and others. The objective is to develop an understanding of the current state and implementation needs required for APPs to engage surgical patients in advanced care planning (ACP) to promote goal concordant care. METHODS/STUDY POPULATION: We will conduct a mixed methods evaluation of ACP knowledge, attitudes, and beliefs amongst surgical APPs to identify barriers and facilitators of APPs engaging in a team-based approach to engaging surgical patients in ACP. We will conduct an online survey and qualitative interviews in the following 4 domains: 1) knowledge, skills, and attitudes about engaging in ACP with a patient or their surrogate decision maker during their perioperative care; 2) prior ACP-specific education; 3) experiences conducting ACP discussions with patients; and 4) perceived training needs to increase ACP uptake and documentation. The findings will provide the foundations to design team-based interventions focused on addressing the barriers and inform training and coaching needs to develop expertise and comfort in the ACP process. RESULTS/ANTICIPATED RESULTS: We expect variability in the knowledge, skills, attitudes, and experiences with the ACP process. We anticipate gaining a better understanding of the educational materials best suited to support APPs as they begin engaging patients in ACP. Possible barriers to APP-led ACP discussions include inconsistent role delineation, uncertainty about the value of pre-operative vs. post-operative ACP discussions, lack of experience engaging in ACP discussion, and lack of familiarity with electronic health records ACP tools. Possible facilitators of APP-led ACP discussions may be related to past work experience settings, exposure to ACP in educational preparation, hands-on observation of value of ACP in surgical patients and influences from attending and residents. DISCUSSION/SIGNIFICANCE: While current ACP research in surgery focuses on physician-led patient engagement in ACP discussions, there is a paucity of research focusing on how to develop a team-based approach to ACP discussions in surgery. This study will provide information necessary for the development of interventions that increase team-based ACP for surgical patients.